Cancer-associated thrombosis during chemotherapy: treatment and prevention: A review - Irina A. Koroleva; Mikhail V. Kopp (ZAO "Consilium Medicum", 2022)
Cancer-associated thrombosis is a significant problem today for both oncologists and vascular surgeons. In patients with malignant neoplasms the incidence of symptomatic venous thromboembolism (VTE) is 47 times higher than in the general population. The presence of distant metastases in solid tumors increases the risk of VTE. Most often, VTE develop in pancreatic cancer and stomach cancer. Chemotherapy increases the risk of developing VTE. Low-molecular-weight heparin and direct oral anticoagulants are used for the treatment of VTE in patients with chemotherapy. The results of the СARAVAGGIO study demonstrated that apixaban is not inferior to dalteparin in the treatment of VTE in patients with active cancer and does not increase the risk of bleeding. Before starting chemotherapy, it is necessary to assess the risk of developing VTE using the Khorana risk score. Outpatient patients with high-risk cancer (Khorana score 2 before the start of a new systemic chemotherapy regimen) may be prescribed thromboprophylaxis with low molecular weight heparin. The idea of using direct oral anticoagulants seems promising, but so far it is beyond the scope of approved indications.